The Quality of life of graduate nursing students in Croatia : a cross-sectional study = Kvaliteta života studenata diplomskog studija sestrinstva u Hrvatskoj : presječna studija - Čivljak, Marta (Array, 2021)
Objective: The objective was to assess the quality of life (QoL) of graduate nursing students enrolled in the University of Zagreb, School of Medicine, and evaluate the relationship between QoL and marital status, age group and work setting. Method: A cross-sectional study was conducted in 2012–2013 among 154 nursing professionals/technicians from the University of Zagreb School of Medicine, Croatia, using the WHOQOL-BREF Questionnaire. Results: The majority of the participants (88.3%) were female, with a median age of 39.0 years (interquartile range, IQR = 31.1–45.2). More than 90% of the participants had already completed university studies. Marital status, age group, or work setting made no significant impact on the scoring of the four QoL domains (physical, psychological, environmental, and social relationships). Significantly lower median values in the psychological domain were noted in the group between 25 and 45 years of age (p = 0.010). Conclusion: Perceptions of QoL might be directly related to the educational levels of the participants since according to the latest knowledge, nurses who are university-educated have better work ability. Providing educational and career prospects can contribute to decreasing nurses" occupational stress levels and increasing their work ability. Other determinants of QoL not addressed in this paper should be investigated.